2018
DOI: 10.1177/2333393618783632
|View full text |Cite
|
Sign up to set email alerts
|

“They Should Be Asking Us”: A Qualitative Decisional Needs Assessment for Women Considering Cervical Cancer Screening

Abstract: In this study, we examine from multiple perspectives, women’s shared decision-making needs when considering cervical screening options: Pap testing, in-clinic human papillomavirus (HPV) testing, self-collected HPV testing, or no screening. The Ottawa Decision Support Framework guided the development of the interview schedule. We conducted semi-structured interviews with seven screen-eligible women and five health care professionals (three health care providers and two health system managers). Women did not per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…In total, we retained 32 studies, four used qualitative (23)(24)(25)(26) and 28 used quantitative methodology (2,(16)(17)(18)(19)(20) . Included studies covered HCPs opinions from five continents: Europe (i.e., UK (47) , Germany (38) and Italy (39) ), North America (i.e., Canada (24,26,35) and the US (2, 16-20, 23, 29-31, 34, 36, 40-44, 46) ), Africa (i.e., Cameroon (28) and Nigeria (25) ), Asia (i.e., China (27) , Jordan (45) ,South Korea (33) and Thailand (37) ) and Oceania (i.e., Australia (32) ). Details of each included study can be found in Appendix A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, we retained 32 studies, four used qualitative (23)(24)(25)(26) and 28 used quantitative methodology (2,(16)(17)(18)(19)(20) . Included studies covered HCPs opinions from five continents: Europe (i.e., UK (47) , Germany (38) and Italy (39) ), North America (i.e., Canada (24,26,35) and the US (2, 16-20, 23, 29-31, 34, 36, 40-44, 46) ), Africa (i.e., Cameroon (28) and Nigeria (25) ), Asia (i.e., China (27) , Jordan (45) ,South Korea (33) and Thailand (37) ) and Oceania (i.e., Australia (32) ). Details of each included study can be found in Appendix A.…”
Section: Resultsmentioning
confidence: 99%
“…(42) . HCPs believe that providing positive HPV test results require appropriate communication strategies to alleviate women's stigma associated with an sexually transmitted infection (STI) diagnosis (26) .…”
Section: Beliefs About Test Efficacymentioning
confidence: 99%
“…“Cervical cancer screening—it's your choice” explicitly acknowledges that women face a decision to undergo cervical cancer screening, and if they choose to participate, they may choose different options because they value the risks and benefits differently. We found in a qualitative needs assessment that some women do not perceive that undergoing cervical cancer screening involves making a decision …”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how women who are racialized, women who have lower levels of education, or women with lower health literacy would perceive the language, presentation, and content of this tool. Because racialized women and women with lower levels of education are less likely to participate in regular screening, and perhaps less likely to face a decision about cervical screening, the perceptions of these populations are important for equitable cervical screening. Because of the small, highly selected sample, a more robust study design, preferably using a probability sample, is required to yield more generalizable conclusions about the tool's ability to elicit informed, values‐based preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation